Selective replication of simian immunodeficiency virus in a subset of CD4+ lymphocytes. - Gallatin, W M (1989)
Although all CD4+ cells theoretically are at risk for infection by human immunodeficiency viruses or the related simian immunodeficiency viruses found in Old World monkeys, only a small proportion of CD4+ lymphocytes from infected individuals have detectable virus. This suggests that immunodeficiency viruses may replicate predominantly in a minor subset or activated form of CD4+ T cells, a possibility we examined in macaques infected with a simian immunodeficiency virus isolate, SIV/Mne. Macaque CD4+ lymphocytes could be divided into two subtypes that differed in their level [high (hi) or low (lo)] of expression of a class of heterotypic adhesion receptors (HARs). In blood from animals infected with SIV/Mne, HARhi CD4+ T cells were lost selectively compared to HARlo CD4+ cells and, when cultured, exhibited 50-fold more recoverable reverse transcriptase activity. The HARhi CD4+ subset was also markedly more susceptible to productive infection following exposure to SIV/Mne in vitro. Both subsets are composed primarily of small resting lymphocytes. However, HARhi cells respond differentially to mitogenic stimulation and may thus be more likely to provide the cellular factors necessary to initiate or enhance virus replication. Thus, HAR expression may prove useful both as a prognostic indicator in immunodeficiency virus infection and as a tool to analyze pathogenesis of immunodeficiency viruses.